Pedagogical Conditions Actualizing the Potential of The Karakalpak Traditions of Labor Education in The Content of Theoretical, Methodological and Practical Training of Students - Userbay Aleuov; Doshniyazov Jarliqasin Qarlibaevich (Zien Journals, 2021)
The article reveals the main labor qualities of the Karakalpaks, highlights the set of pedagogical conditions and traditions of labor education in the content of theoretical, methodological and practical training of students; influence of different genres and types of activities (games, fairy tales, songs, stories, sayings, etc.) for the labor education of children; in the course of the research, the main labor qualities of the Karakalpaks were determined
Keywords: folk pedagogy; labor qualities; pedagogical conditions; pedagogical potential